2008
DOI: 10.1007/s11430-008-6025-6
|View full text |Cite
|
Sign up to set email alerts
|

Total alkyl dibenzothiophenes content tracing the filling pathway of condensate reservoir in the Fushan Depression, South China Sea

Abstract: The condensates are generally characterized by high maturity, low concentration of steranes and terpanes biomarkers and low content of non-hydrocarbon fraction. In this case commonly used steranes, terpanes and carbazoles parameters cannot be effectively applied in the reservoir-filling tracing. The hydrogen bond formed by sulfur atom in the dibenzothiophenes (DBTs) results in molecule adsorption and fractionation during oil migration in reservoir. Like carbazoles, total DBTs content decreases with the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…(e) (f) As demonstrated by previous studies, the relative abundances of methylated DBT isomers and the absolute concentrations in oils are also relative to migration distance. Therefore, the ratios of methylated DBT isomers and concentrations of total DBTs for oils derived from same source bed/kitchen can be applied to trace oil migration direction and charging pathway (Wang et al 2004;Li et al 2008Li et al , 2014aFang et al 2016Fang et al , 2017a. Except for one case study in a Tertiary sandstone reservoir in the Beibuwan Basin, South China Sea, we also found that the absolute concentration of DBTs was not an effective indicator for tracing oil migration orientation in Tarim Paleozoic carbonate reservoirs (Li et al, unpublished data).…”
Section: The Extent Of Biodegradation and Water Washingmentioning
confidence: 88%
“…(e) (f) As demonstrated by previous studies, the relative abundances of methylated DBT isomers and the absolute concentrations in oils are also relative to migration distance. Therefore, the ratios of methylated DBT isomers and concentrations of total DBTs for oils derived from same source bed/kitchen can be applied to trace oil migration direction and charging pathway (Wang et al 2004;Li et al 2008Li et al , 2014aFang et al 2016Fang et al , 2017a. Except for one case study in a Tertiary sandstone reservoir in the Beibuwan Basin, South China Sea, we also found that the absolute concentration of DBTs was not an effective indicator for tracing oil migration orientation in Tarim Paleozoic carbonate reservoirs (Li et al, unpublished data).…”
Section: The Extent Of Biodegradation and Water Washingmentioning
confidence: 88%
“…These molecular indicators were successfully applied in Tertiary sandstone reservoirs in the north margin basins of the South China Sea (Wang et al 2004a;Li et al 2008) and in the Ordovician carbonate reservoir of a karst pore-fissurenetwork type in the Tahe and Halahatang Oilfields of the Tarim Basin (Wang et al 2004aLi et al 2014a, b;Fang et al 2016). The results suggest that these parameters can be used as an effective tracing indicator for oil filling orientation and migration pathways.…”
Section: Oil Charging Orientation and Filling Pathwaysmentioning
confidence: 99%
“…But the other three are applicable over a wide range of maturity and correlate well with each other; therefore, this paper chose Ts/ (Ts + Tm) and C 29 Ts/C 29 H as representative for the next study ( Figure 7). Previous studies (Fang et al, 2016;Li et al, 2008;Wang, He, Li, Hou, & Guo, 2004) have demonstrated that the parameters of alkyl dibenzothiophene (dibenzothiphenes, methyldibenzothiphenes…”
Section: Migration Characteristics and Directionmentioning
confidence: 99%